The effectiveness of the FIFA11+ program across the population - Meyer, T. K. (Journal of Australian Strength and Conditioning, 2019)
This article reviews the literature regarding the FIFA11+ program and its effects on injury prevention and athletic performance across a broad population. The FIFA11+ program has been shown to significantly reduce the risk of injuries in soccer players.